Citrullinated Histone H3 Level as a Novel Biomarker in Pediatric Clinical Sepsis - Ronald Chandra; Antonius Hocky Pudjiadi; Rismala Dewi (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Sepsis is still leading cause of death in critically ill children. Early recognition of sepsis and treatments are needed to reduce its mortality. The use of citrullinated Histone H3 (Cit-H3) as an early sepsis marker and outcome predictor has been validated in previous studies among adults. However, only one study in pediatric meningococcal sepsis was reported with contradictory results. This study aims to determine Cit-H3 levels in pediatric clinical sepsis and analyze its association with sepsis severity and survival rate.METHODS: A prospective observational cohort study involving 67 pediatric subjects clinically diagnosed with sepsis was conducted. Cit-H3 levels, Pediatric Logistic Organ Dysfunction-2 (PELOD-2) score, and Pediatric Sequential Organ Failure Assessment (pSOFA) score were assessed at the time of diagnosis (0-hour) and 48 hours later. Pearson Correlation test was used to determine the correlation between Cit-H3 levels with PELOD-2 and pSOFA scores and receiver operating curve to find the cut-off of Cit-H3 levels on clinical sepsis patients.RESULTS: Among clinically sepsis patients, the median Cit-H3 level was 1,210 (800-32,160) ng/mL, with optimal cut-off point ≥1200 ng/mL (sensitivity 83.3% and specificity 75.7%) to discriminate sepsis. The median Cit-H3 levels at 0-hour were lower in survivor compared to non-survivor group (p=0.016). Cit-H3 level was able to predict mortality with optimal cut-off point ≥1,200 ng/mL, sensitivity 72.2% and specificity 57.1% (AUC of 69.2%; p=0.017). Using survival analysis, Cit-H3 was significantly associated with the mortality rate (p=0.023; hazard ratio of 3.45).CONCLUSION: Cit-H3 level could be potential to predict pediatric sepsis events and its outcome.KEYWORDS: citrullinated histone H3, neutrophil extracellular traps, pediatric sepsis, PELOD-2 score, pSOFA score, survival